Предмет: Алгебра,
автор: cookietimemail
Решите уравнение (х+3) (х2- 3х + 9) = 91
Ответы
Автор ответа:
0
Ответ: x=4.
Объяснение:
Автор ответа:
0
Ответ:
x = 4.
Пошаговое объяснение:
(х + 3) (х² - 3х + 9) = 91;
[-] Заметим одну из формул сокращённого умножения - сумму кубов:
(a + b) (a² - ab + b²) = a³ + b³.
Воспользуемся данной формулой:
x³ + 3³ = 91;
x³ + 27 = 91;
x³ = 91 - 27;
x³ = 64;
x = ³√64;
x = 4.
_____________
Удачи Вам! :)
Похожие вопросы
Предмет: Физика,
автор: anastasiazitnik8
Предмет: Математика,
автор: diana87bila
Предмет: Информатика,
автор: MrLukes
Предмет: Геометрия,
автор: avamika